2020
DOI: 10.18280/acsm.440610
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Blended Geopolymer Concrete Using Ultrafine Ground Granulated Blast Furnace Slag and Copper Slag

Abstract: This paper presents the properties of blended geopolymer concrete manufactured using fly ash and ultrafine Ground Granulated Blast Furnace Slag (UFGGBFS), along with the copper slag (CPS) as replacement of fine aggregate (crushed stone sand). Various parameters considered in this study include different sodium hydroxide concentrations (10M, 12M and 14M); 0.35 as alkaline liquid to binder ratio; 2.5 as sodium silicate to sodium hydroxide ratio and cured in ambient curing condition. Further, geopolymer concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Rathanasalam et al [ 145 ] investigated different sodium hydroxide (NaOH) molarities of 10 M, 12 M, and 14 M and developed a mixture utilising 5%, 10%, and 15% ultrafine ground granulated blast furnace slag (UFGGBFS) replacing fly ash, with crushed stone or copper slag. After curing for 3, 7, and 28 days at 60 °C, the compressive strength was evaluated.…”
Section: Injection Moulding Processmentioning
confidence: 99%
“…Rathanasalam et al [ 145 ] investigated different sodium hydroxide (NaOH) molarities of 10 M, 12 M, and 14 M and developed a mixture utilising 5%, 10%, and 15% ultrafine ground granulated blast furnace slag (UFGGBFS) replacing fly ash, with crushed stone or copper slag. After curing for 3, 7, and 28 days at 60 °C, the compressive strength was evaluated.…”
Section: Injection Moulding Processmentioning
confidence: 99%
“…The highest porosity was provided by F8 mix, which increases the open porosity about 25% compared to control mix F0. Previous studies [10] have shown that the use of GBFS lead to a low hydration rate of binders, which means that the specimens with low levels of PC lead to a micro-structure low densification due to insufficient hydrates development and consequently porosity increases.…”
Section: Figure 6 Effect Of Combined Gbfs Ces and Bw On Open Porositymentioning
confidence: 99%
“…The blending of GBFS as a raw material in the concrete, mortar and cement sectors to substitute a part of cement or fine aggregates is studied by many [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…GPC produced with blended source materials exhibits increased and high early strength. Vijayasarathy et al [ 52 ] presented the properties of binary blend geopolymer concrete and revealed that the addition of GGBS with fly ash to GPC increased the strength performance up to 25%. The effect of adding sugarcane bagasse ash as a partial alternative for GGBS in GPC was investigated by Kathirvel et al [ 53 ], who found that the replacement was effective in terms of improving the fresh and hardened properties up to a maximum of 40%.…”
Section: Introductionmentioning
confidence: 99%